Barfing in the backseat : how I survived my family road trip - Winkler, Henry, 1945- (New York, N.Y., U.S.A. Grosset & Dunlap, 2007)
Hank must work on a huge homework packet during a family trip to North Carolina or he will spend the day with his father at a crossword puzzle tournament rather than riding roller coasters with his mother, sister, and friend Frankie.
"The world's greatest underachiever."
Keywords: Automobile travel -- Juvenile fiction; Homework -- Juvenile fiction; Family -- Juvenile fiction; Crossword puzzles -- Juvenile fiction; Learning disabilities -- Juvenile fiction; Humorous fiction